Analisis Permasalahan Hukum E-Commerce dan Pengaturannya di Indonesia - Tansah Rahmatullah (Jurnal Media Justitia Nusantara, 2017)
E-commerce has a unique characteristic where transactions can be done anywhere, anytime, in a flexible way and carried out online, but can cause legal certainty, namely whether the trade transaction is lawful, fulfilling the elements of validity, jurisdiction, and legal protection. whether it is related to buying and selling transactions or related to the use of personal data (collecting). This study uses a normative juridical research method by reviewing and analyzing secondary data in the form of primary legal materials, secondary and tertiary legal materials. The specification of this study is descriptive analytical research to describe and analyze e-commerce problems through the library research approach which will be presented descriptively. This normative legal research uses secondary data types because it focuses more on library research. Based on research, in addition to the existing positive laws related to civilization, namely the Civil Code, Indonesia has the ITE Law and the Trade Law as well as the Government Regulation on the Implementation of Electronic Transactions and Systems which is the legal umbrella of e-commerce transactions, however harmonization is needed for activities e-commerce has legal certainty and guarantees protection. In fact, given its unique characteristics of e-commerce activities, a selfregulation (Sui Generis) is needed, like the Personal Data Protection Act.